The isolation, total synthesis and structure elucidation of chlorofusin, a natural product inhibitor of the p53–MDM2 protein–protein interaction - Clark, Ryan C.; Lee, Sang Yeul; Searcey, Mark; Boger, Dale L. (Natural product reports, 2009)
Inhibitors of key protein-protein interactions are emerging as exciting therapeutic targets for the treatment of cancer. One such interaction between MDM2 (HDM2) and p53, that silences the tumour suppression activities of p53, was found to be inhibited by the recently isolated natural product chlorofusin. Synthetic studies on this complex natural product summarized herein have served to reassign its chromophore relative stereochemistry, assign its absolute stereochemistry, and provided access to a series of key analogues and partial structures for biological evaluation.